Numerical studies on yield line patterns of thread-fixed one-side bolted endplate connection to square hollow section column under tension. (October 2020) - Zhang, Yue; Wang, Peijun; Liu, Mei; Liu, Yuanjian; Zhang, Boxun; Zhou, Shengzhan; Chen, Junxia
Abstract: Numerical analyses on yield line patterns of Thread-fixed One-side Bolts (TOBs) bolted endplate connection to Square Hollow Section (SHS) column under tension were presented. A finite element model was established and verified by test results carried out by the authors. Parametric analyses were carried out to investigate the effects of the bolt diameter and the column wall thickness on the connection behavior. Analysis results showed that the yield strength of connection increased with the increase in the bolt diameter and the column wall thickness. The relationship between the connection failure mode and the bolt diameter to the column wall thickness ratio was presented. The brittle failure of the connection could be avoided if the ratio was out of a certain range. A new dumbbell yield line pattern for connections failed by column wall yield failure was proposed and the yield strength design model corresponding to the dumbbell yield line pattern was proposed. The proposed analytical method could predict the yield strength of the TOBs bolted connection accurately. Graphical abstract: Unlabelled Image Highlights: Yield patterns of T-stubs bolted by Thread-fixed One-side Bolts (TOBs) were studied. Effects of column wall thickness and bolt diameter on yield pattern were presented. A new dumbbell yield pattern for column wall failed by complete yielding was presented. Design method for tensile strength corresponding to dumbbell yield pattern was proposed.